A Broadband and High Gain Tapered Slot Antenna for W-Band Imaging Array Applications - Dong Sik Woo; Kang Wook Kim; Hyun-Chul Choi (International Journal of Antennas and Propagation)
A broadband and high gain tapered slot antenna (TSA) by utilizing a broadband microstrip- (MS-) to-coplanar stripline (CPS) balun has been developed for millimeter-wave imaging systems and sensors. This antenna exhibits ultrawideband performance for frequency ranges from 70 to over 110 GHz with the high antenna gain, low sidelobe levels, and narrow beamwidth. The validity of this antenna as imaging arrays is also demonstrated by analyzing mutual couplings and 4-element linear array. This antenna can be applied to mm-wave phased array, imaging array for plasma diagnostics applications.